Rapid Analysis of Heavy Metal Element Adsorption by SCG Based on LIBS Technology - Xie Hairui; You Libing; Fang Xiaodong; Li Leyi; Ding Haokai; Zhou Zhengqi; Zhang Guanyang; Zhang Dongjian (E3S Web of Conferences)
Rapid evaluation and real-time detection of adsorption materials are particularly critical in the adsorption treatment of heavy metal wastewater. However, most elemental analysis methods have complex pretreatment procedures and are time-consuming, making real-time analysis difficult to achieve. A laser-induced breakdown spectroscopy device with a 248nm KrF excimer laser as the excitation source was used to study the rapid test of heavy metal content in wastewater absorbed by coffee grounds (SCG). This study prepared 16 sets of spent coffee grounds calibration samples and 8 sets of SCG adsorption samples by externally adding heavy metal elements. After optimizing the experimental system, the characteristic spectral lines of Cd II 226.510nm and Cu I 324.754nm were analyzed. Using Cu as the internal standard element, the Cd/Cu intensity ratios from the spectral tests of 16 calibration samples were fitted with the different Cd mass fractions in SCG to obtain a calibration model, with the polynomial fitting determination coefficient (R²) reaching 0.998. Eight adsorption samples were tested, and the calibration model was used to analyze the adsorption capacity of SCG for Cd solutions of different concentrations. The adsorption rate increased with the concentration of Cd solution, reaching a maximum of 18.96 mg/g. This work provides a reference for the rapid elemental analysis of adsorbent materials during the adsorption treatment of heavy metal wastewater.